VD_FINDINFO Décision / 2021 / 227 vom 27. Januar 2021 - VD Tribunal cantonal (2021)
NON-LIEU, DIFFAMATION, INSOUMISSION À UNE DÉCISION DE L'AUTORITÉ, DÉNONCIATION CALOMNIEUSE | 14 CP, 173 CP, 292 CP, 303 CP, 310 CPP (CH)